2022
DOI: 10.1186/s40779-022-00386-z
|View full text |Cite
|
Sign up to set email alerts
|

Nanosensitizers for sonodynamic therapy for glioblastoma multiforme: current progress and future perspectives

Abstract: Glioblastoma multiforme (GBM) is the most common primary malignant brain tumor, and it is associated with poor prognosis. Its characteristics of being highly invasive and undergoing heterogeneous genetic mutation, as well as the presence of the blood–brain barrier (BBB), have reduced the efficacy of GBM treatment. The emergence of a novel therapeutic method, namely, sonodynamic therapy (SDT), provides a promising strategy for eradicating tumors via activated sonosensitizers coupled with low-intensity ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 121 publications
(121 reference statements)
0
25
0
Order By: Relevance
“…Nevertheless, most of these sonosensitizers has short half-life, poor in vivo targeting and water solubility, making it difficult to be enriched at the tumor site. With remarkable advancements in nanotechnology, nanomaterials have been introduced as an alternative route to overcome the above issues of traditional sonosensitizers and increasing number of nano-sonosensitizers have been designed and widely used recently ( Guo et al, 2022 ). As for ultrasound, studies mainly concentrated on ultrasound setting parameters including frequency, intensity, transducer geometry, coupling media, as well as other experimental conditions that could affect reproducibility and transferability ( Secomski et al, 2017 ; Araújo Martins et al, 2021 ; Tamboia et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, most of these sonosensitizers has short half-life, poor in vivo targeting and water solubility, making it difficult to be enriched at the tumor site. With remarkable advancements in nanotechnology, nanomaterials have been introduced as an alternative route to overcome the above issues of traditional sonosensitizers and increasing number of nano-sonosensitizers have been designed and widely used recently ( Guo et al, 2022 ). As for ultrasound, studies mainly concentrated on ultrasound setting parameters including frequency, intensity, transducer geometry, coupling media, as well as other experimental conditions that could affect reproducibility and transferability ( Secomski et al, 2017 ; Araújo Martins et al, 2021 ; Tamboia et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have demonstrated that many chemical products such as porphyrin and its derivatives, cisplatin, fluoroquinolone agents, etc., were able to act as sonosensitizers ( Chen et al, 2014 ; Pang et al, 2016 ). Meanwhile, with the rapid advancement of nanotechnology in recent years, certain rationally designed biocompatible nanomaterials have shown great potential in SDT, which further motivated the development of SDT against cancer ( Qian et al, 2016 ; Mohapatra et al, 2021 ; Guo et al, 2022 ; Zhu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tumor selectivity can be further enhanced by protonation of ionizable carriers in the acidic environment outside glioma cells. Sonodynamic therapy [ 172 ] and radiation therapy [ 172 ] for glioblastoma have been studied extensively in the past. Nowadays, IDDSs are expected to provide better therapeutic results.…”
Section: Applications Of Iddss In the Treatment Of The Diseasesmentioning
confidence: 99%
“…Sonodynamic therapy (SDT) refers to sonochemical or sonophotochemical events in the acoustic field that result in cytotoxicity dependent on the sensitizer [ 21 ]. US-mediated SDT has already been used as a well-established anti-tumor treatment strategy [ [22] , [23] , [24] , [25] ], which can promote tumor cell killing by accredited mechanisms, including the generation of ROS and ultrasonic cavitation [ 26 ]. Recently, US-mediated SDT has been applied in antimicrobial therapy [ 27 ].…”
Section: Introductionmentioning
confidence: 99%